Export Performance of Mango Fruit from India - N. R. Mamie Desai; G.K. Hiremath; J. S. Hilli (Journal of Agricultural Extension Management, 2025)
The new economic policy initiated in early nineties in our country has ushered in the age of economic liberalization. Consequently, it has thrown up many challenges as well as opportunities for India’s agricultural exports in general and horticultural exports in particular. Even though the economic liberalization programme is primarily focused on agriculture, the strategy of reforms is aimed at creating a more favourable policy framework for agricultural development and much more needs to be done in this area. With the signing of the agreement on the Dunkel Draft Report, which gave rise to the World Trade Organization (WTO) in January 1995, the international trade situation has undergone a change, one of the main results of which will be to provide opportunities for enhanced agricultural exports over time. Trade in agricultural goods can play a significant role in promoting economic development, especially in developing countries where the majority of the population is engaged in agriculture